Human and nature relations in Hooykaas Christiaan’s Enige Sasakse Volksvertelsels (Lombok): An ecocritical study - Hilmi, Hubbi Saufan; Andayani; Wardani, Nugraheni Eko (Research Journal in Advanced Humanities, 2024)
This study explores the intricate relationship between humans and nature, as depicted in the Sasak tribal folklore “Enige Sasakse Volksvertelsels (Lombok)” by Dr. C. Hooykaas employs Greg Garrard’s literary ecocriticism. The Sasak folklore delineates the human-nature relationship into two facets: humans as subjects and humans as objects in relation to nature. The former portrays humans viewing nature as the mother of Earth, guided by the ethics of care and a holistic understanding of nature. Conversely, the latter reveals instances of violence and exploitation of nature. By examining these dimensions, this research aims to foster discussions on environmental conservation and integrate awareness regarding its significance. Furthermore, this study contributes to the expansion of literary criticism, particularly within the realm of literary ecocriticism. It serves as a valuable initiative for preserving the local wisdom and folklore of the Sasak people on Lombok Island, Indonesia, emphasising the urgency of environmental consciousness.